Evaluation of Information Quality on the Instagram Social Media of Bekasi Regency General Hospital - Mahdi, Askarul; Hidayanto, Achmad Nizar (Syntax Literate, 2026)
Abstract - This study aims to evaluate the quality of information on the Instagram social media of the Bekasi Regency General Hospital (RSUD), focusing on two main aspects, namely brand awareness and education. The method used in this study is Importance-Performance Analysis (IPA) which maps the gap between user expectations and reality on information quality. The data was obtained through a questionnaire survey that was distributed to Instagram social media visitors of the Bekasi Regency General Hospital. The results of the study show that the dimensions of timeliness and completeness require the highest improvement priority to increase brand awareness and education. The dimensions of credibility and accuracy have good performance and need to be maintained. This research provides practical recommendations for the management of Bekasi Regency Hospital to improve the quality of information presented on their Instagram social media.